Fatigue crack growth in the micro to large scale of 7075-T6 Al sheets at different R ratios. (June 2016) - Tang, K.K.; Berto, F.; Wu, H.
Highlights: SED criterion is employed to formulate a multiscale fatigue crack growth model. Material, loading and geometry effects are incorporated in the model by TFs. Effects of R ratios on fatigue behaviors of 7075-T6 Al sheets are discussed. Transitionalized crack length and fictitious crack length are defined and compared. Abstract: Transitionalized crack length (TCL) is derived from energy density based Δ S (incremental strain energy density factor) model that is inherently multiscaling, which is in contrast to the fictitious crack length (FCL) generated from da / dN –Δ K (incremental stress intensity factor) model. By employing transitional functions (TFs), the effects of material, loading and geometry (MLG) are incorporated and reflected in the multiscale fatigue crack growth process of 7075-T6 Al sheets. The constant change of MLG in metal fatigue is necessitated by the effects of Non-equilibrium and non-homogeneity (NENH). Variation of R ratios leads to the change of TFs accordingly. Particularly discussed are the effects of TFs on the fatigue crack growth of 7075-T6 Al sheets. Results turn out that TCLs have a relatively better agreement with test data than FCLs. The proposed model can possibly offer a predictive calibration for the Δ K model.